2007
DOI: 10.1007/s11325-007-0133-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cognitive performance among different age groups in patients with obstructive sleep apnea

Abstract: The aim of this study was to evaluate the effect of obstructive sleep apnea syndrome on the cognitive performance of young and middle-aged patients. Patients were divided into two groups, one consisting of 30 patients less than 50 years of age and the other consisting of 28 patients 50 years and over. Normal subjects were similarly divided into two groups, composed of 17 younger and 24 older controls. Patients and controls were examined with all-night polysomnography and subsequently underwent cognitive testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 33 publications
6
40
0
3
Order By: Relevance
“…Our behavioral findings are consistent with previous reports that OSA does not impair performance relative to age-matched control subjects until patients reach middle-age (15). The authors of that study concluded that OSA-related factors, such as sleep fragmentation or brain damage due to hypoxia for many years, may lead to these cognitive differences, and that patients with OSA are particularly vulnerable to cognitive impairment when they reach middle age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our behavioral findings are consistent with previous reports that OSA does not impair performance relative to age-matched control subjects until patients reach middle-age (15). The authors of that study concluded that OSA-related factors, such as sleep fragmentation or brain damage due to hypoxia for many years, may lead to these cognitive differences, and that patients with OSA are particularly vulnerable to cognitive impairment when they reach middle age.…”
Section: Discussionsupporting
confidence: 92%
“…Alchanatis and colleagues (15) reported that middle-aged patients with OSA showed cognitive decline in comparison to age-matched control subjects, whereas cognitive performance of younger patients with OSA on attention tasks was similar to age-matched control subjects. This suggests that age plus OSA may pose a double insult for which the brain may be not able to compensate.…”
mentioning
confidence: 98%
“…It is reported that cognitive functions are worse in hypoxemic OSAS patients than in non-hypoxemic ones [34]. Also the individual factors such as age and obesity have an important effect on cognitive dysfunction [35][36][37]. It is suggested that intermittant hypoxemia, daytime sleepiness and obesity may have an effect on neurocognitive dysfunction in OHS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive impairment seen in OSA tends to be more significant with increasing age (24)(25)(26), suggesting that older age groups are more susceptible to the effects of OSA on the brain (27), or that compensatory mechanisms that are perhaps present in younger people and help to recruit other areas of the brain to maintain performance, may no longer be as proficient (28). OSA is increasingly prevalent with age (29), although there tends to be less reported sleepiness in older patients.…”
Section: Review Articlementioning
confidence: 99%